Looking for an ideal coma scale: It is time to replace GCS (Bangladesh Critical Care Journal, 2014)
No Abstract AvailableDOI: http://dx.doi.org/10.3329/bccj.v2i1.19948 Bangladesh Crit Care J March 2014; 2 (1): 1-3